Information Communication Technology and Social Studies Instruction in Delta State, Nigeria - Atubi, Onamrewho Favour (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2022)
Introducing Information Communication Technology (ICT) resources and skills to Social Studies as instructional materials and aids can provide an accessible and flexible Social Studies education at the primary and secondary school levels in Delta State. Hence the aims of this study were to consider various ICT resources that can be harnessed and used by Social Studies teachers for social studies instructions; outline the benefits of ICT to students and teachers of Social Studies and identify the challenges affecting its usage for Social Studies instructions in Delta State. The study employed the survey research design, a sample of sixty (60) Social Studies teachers from six primaries and six Junior Secondary Schools selected randomly from six Local Government Areas of the state. The main instrument for data collection was a well- structured questionnaire designed to obtain data and centered around the main objectives of the study. Sixty (60) copies of the questionnaire were distributed and sixty (60) copies were retrieved and used for data analysis. While data gathered were analyzed using statistical tools of mean and percentages. The result revealed that ICT resources and skills such as android phones, internet browsing, power point projection, virtual learning and computers assist in teaching Social Studies concepts. Secondly, the study revealed that ICT skills and facilities contribute meaningfully to Social Studies instructions when used by teachers, students will derive holistic knowledge when taught with ICT tools. Meanwhile the findings showed that there exist many setbacks and challenges in ICT usage such as funding, capacity building and lack of electricity supply amongst others. Based on these findings, one of the recommendations made was that stakeholders in the education sector both government and private organizations, should be concerned with the provision of ICT facilities in primary and junior secondary schools across Delta State.